2022
DOI: 10.1001/jamanetworkopen.2022.4492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tacrolimus vs Intravenous Cyclophosphamide on Complete or Partial Response in Patients With Lupus Nephritis

Abstract: Key Points Question What is the efficacy and safety of tacrolimus vs intravenous cyclophosphamide (IVCY) as initial therapy for lupus nephritis (LN) among Chinese patients? Findings In this randomized clinical trial of 299 patients, the complete or partial kidney response rate was 83.0% with tacrolimus vs 75.0% with IVCY after 24 weeks of treatment, and tacrolimus was statistically noninferior to IVCY regarding response rate. The incidence and type of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
0
7
0
3
Order By: Relevance
“…While the overall standardized incidence ratio of cancer is higher in SLE patients, administration of CP has been shown to increase the incidence of cancers, particularly those of the urinary tract, bone marrow, and skin, prompting the use of combination therapy to prevent these side effects [89]. A recent randomized clinical trial in Chinese SLE patients comparing cyclophosphamide and tacrolimus has shown that tacrolimus has a marginally higher rate of complete response and faster recovery of kidney function [90]. In contrast to this, another trial showed that combination therapy of cyclophosphamide with rituximab followed by belimumab not only lowered the maturation of transitional to naive B cells during B-cell reconstitution but also improved the negative selection of autoreactive B cells, thereby proving beneficial over the conventional cyclophosphamide and belimumab combination [91].…”
Section: Cyclophosphamidementioning
confidence: 99%
“…While the overall standardized incidence ratio of cancer is higher in SLE patients, administration of CP has been shown to increase the incidence of cancers, particularly those of the urinary tract, bone marrow, and skin, prompting the use of combination therapy to prevent these side effects [89]. A recent randomized clinical trial in Chinese SLE patients comparing cyclophosphamide and tacrolimus has shown that tacrolimus has a marginally higher rate of complete response and faster recovery of kidney function [90]. In contrast to this, another trial showed that combination therapy of cyclophosphamide with rituximab followed by belimumab not only lowered the maturation of transitional to naive B cells during B-cell reconstitution but also improved the negative selection of autoreactive B cells, thereby proving beneficial over the conventional cyclophosphamide and belimumab combination [91].…”
Section: Cyclophosphamidementioning
confidence: 99%
“…Another randomized, open-label, parallel control, and noninferiority study found tacrolimus was noninferior to IV CY for LN response at week 24. There was a complete or partial response rate of 83.0% (117 of 141 patients) in the tacrolimus group and 75.0% (93 of 124 patients) in the IV CY group [ 56 ]. Results of representative studies of cyclophosphamide treatment compared to MMF or calcineurin inhibitors in patients with lupus nephritis were summarized in Table 2 .…”
Section: Clinical Use Of Cy In Induction Remission In Lnmentioning
confidence: 99%
“… 137 Recently, a phase 3 study with 314 LN patients supports oral tacrolimus to be non-inferior to cyclophosphamide in induction therapy for LN, showing a more favorable safety profile than cyclophosphamide. 138 In LN patients who failed to achieve complete response after standard induction therapy, thus having a refractory condition, might profit from multitarget therapy, especially if proteinuria persists. This treatment can help patients achieve a renal response and reduce the use of steroids.…”
Section: Targeting Lupus To Control Lupus Nephritismentioning
confidence: 99%